Geographic Distribution of Foot and Ankle Orthopaedic Surgeons Throughout the United States. Issue 4 (22nd October 2020) - Zhang, Hui; Fanelli, Matthew G.; Cush, Coleman; Wagner, Benjamin; Grandizio, Louis C.; Young, Amanda; Maddineni, Bhumika; Cush, Gerard J.
Category: Other Introduction/Purpose: Orthopaedic Surgery has become increasingly subspecialized since fellowships were established in the 1970s. Previous investigations within hand and urologic surgery have demonstrated an uneven geographic distribution within these subspecialties. Economic factors can influence surgeon distribution within a particular geographic region. At present, the geographic distribution of orthopaedic foot and ankle (OFA) surgeons in the US is poorly defined. The purpose of this investigation is to determine the geographic distribution of OFA surgeons in the US. We hypothesize that there will be substantial differences in OFA surgeon density throughout the US and that economic factors may play a role in access to subspecialty OFA care. Methods: A current membership list was obtained from the American Orthopaedic Foot & Ankle Society (AOFAS). Active AOFAS members were categorized relative to states and US House of Representatives Congressional Districts. Using publicly available census data, we recorded the population within each state and district as well as the percentage of families and people with income below the federally defined poverty level. Descriptive statistics were utilized for demographic information. The relationship between income level and the number of surgeons was determined using a Pearson correlation. These data were used to generate OFA surgeons per capita at a state and congressional district level. This information was also used to generate choropleth maps comparing surgeon density and poverty. Results: We identified a list of 1, 103 active AOFAS members with 1, 311 practice addresses. There was an average of 21.2 OFA surgeons per state. There was an average of 0.38 and 0.40 OFA surgeons per 100, 000 people in each state and congressional district respectively. The District of Columbia, VT, WY, and NE had the highest OFA surgeon density. WV, KY, NM, RI had the lowest density. 75 congressional districts had no OFA surgeons. There was a statistically significant negative relationship demonstrating that regions with higher levels of poverty had fewer OFA surgeons, with a Pearson correlation coefficient of -0.14, (P-value = 0.008). This relationship is further illustrated in Figure 1. Conclusion: There is wide geographic variation of OFA surgeon density throughout the US. Regions with higher levels of poverty have less access to OFA surgeons compared to regions with lower poverty levels. Understanding these trends may aid in developing both recruitment and referal strategies for complex foot and ankle care in underserved regions.